PERKEMBANGAN BERMAIN DALAM PERMAINAN TRADISIONAL (CONGKLAK) UNTUK MELATIH MOTORIK KASAR, SOSIAL DAN EMOSIONAL PADA ANAK USIA DINI - Indar Rahman, Khofifah; Khadijah (LPPM STAI Muhammadiyah Probolinggo, 2023)
Playing is every child's desire. Play is also defined as a place for children to express all forms of behavior that are fun and without coercion.